Handicraft Tourism in Pokhara: Connecting the Past Tradition to the Present - Upadhyay, Prakash (Journal of Nepalese Business Studies, 2019)
Although the importance of handicraft has been widely recognized, the literature regarding the role of handicraft in tourism market is scarce. Based on empirical data, the present article aimed to explore the interplay between handicraft and tourism, the contribution of handicraft in tourism promotion and the challenges faced by handicraft sector in Pokhara, Nepal. This study identifies that there is a significant level of correlation and dependency between handicraft and foreign tourist arrivals, job creation and the increase in income and social status of handicraft shop proprietor. As a harbinger of past tradition, handicraft tourism/souvenir items has created a unique experience for tourist, enriched nation’s pride, belief and identity and connected the past tradition to the present. Lack of effective advertisement/marketing, inequitable price, scarcity of raw materials, intrusion of foreign goods, ineffective government policies are the key challenges of handicraft tourism. Policy improvement, increase in source/supply of raw materials, supply of handicrafts as per demand, creative production and marketing are the ways that can promote handicraft market. Handicraft tourism is not just about displaying and selling products, it is about allowing tourists to truly understand the skill/craft at rear and realize handicrafts unique tradition, linking tourists to artisans to facilitate them understand and appreciate the art. It is necessary recognizing the importance of local handicraft in sustainable tourism development and the importance of tourism as an agent for protection and preservation of traditional crafts, methods of production and cultural milieu.